Hasan Âli Yücel dönemi Milli Eğitim Bakanlığı Kültür Yayınları'nın Erken Cumhuriyet Dönemi kültür politikalarındaki rolü - Yakup, Bilal (My University, 2025)
Hasan Âli Yücel dönemi Milli Eğitim Bakanlığı Kültür Yayınları'nın Erken Cumhuriyet Dönemi kültür politikalarındaki rolü = Abstract Bu çalışma, Hasan Âli Yücel'in Eğitim Bakanı olduğu 1939-1946 yılları arasında Milli Eğitim Bakanlığı Yayınları'nın kültür eserlerini incelemektedir. Araştırma, yayın sayısındaki niceliksel artışın ve edebiyat, felsefe, tarih, eğitim ve bilimsel eserler gibi alanlarda niteliksel çeşitliliğin, Cumhuriyet'in ilk yıllarında Türkiye'nin kültür politikasının somut bir tezahürü olduğunu ortaya koymaktadır. Hasan Âli Yücel'in önderliğinde yürütülen faaliyetler, devlet tarafından sistematik bir çeviri politikası ve edebi kanonun oluşturulmasını sağlamıştır. Özel yayıncılık alanında öncü olan Tercüme dergisi ve MEB Yayınları, klasik eserlerin yayılmasına ve kültürel yayınlara erişimin kolaylaşmasına katkıda bulunarak, Türk kültürünün modernleşmesinde yazılı kültürel eserlerin sistematik oluşumunda belirleyici bir rol oynamıştır. Çalışma, devletin liderliğinin kalıcı bir kültürel dönüşüm yarattığını ortaya koymakta ve Erken Cumhuriyet döneminin kültür politikalarının başarısını MEB Yayınları bağlamında somut verilerle ortaya koymaktadır.

The role of the ministry of national education cultural publications during the Hasan Ali Yücel era in the cultural policies of the early republican period The focus of this study is an examination of the cultural works published by the Ministry of National Education between 1939 and 1946, during the period in which Hasan Âli Yücel was Minister of Education. The research reveals that the quantitative increase in the number of publications and the qualitative diversity in fields such as literature, philosophy, history, education, and scientific works constitute a concrete manifestation of Turkish cultural policy in the early years of the Republic. The activities carried out under the leadership of Hasan Âli Yücel ensured the establishment of a systematic translation policy and literary canon by the state. The Tercüme magazine and MEB Publications, which were pioneers in the field of private publishing, contributed to the dissemination of classical works and the facilitation of access to cultural publications. These publications played a decisive role in the systematic formation of written cultural works in the modernization of Turkish culture. The study demonstrates that the state's leadership created a lasting cultural transformation and highlights the success of the cultural policies of the Early Republican period through concrete data within the context of MEB Publications.
The role of the ministry of national education cultural publications during the Hasan Ali Yücel era in the cultural policies of the early republican period
Keywords: cultural policy; Early Republic; Erken Cumhuriyet; Hasan Âli Yücel; kültür; Milli Eğitim Bakanlığı Kültür Yayınları; Millî Eğitim Bakanlığı Yayınları; politikası; Publishers and publishing; tercüme faaliyetleri Ministry of National Education Publications; translation activities; Yayıncı ve yayıncılık; Yücel, Hasan Ali, 1897-1961